How the Merdeka Curriculum Implementation and Teacher Motivation Shape High School Performance Outcomes in West Aceh, Indonesia - Syukri, Shara; Ismail, Ismail; Sofyan, Hizir (Heca Sentra Analitika, 2025)
This study examines the effects of the Merdeka Curriculum implementation and teacher motivation on high school teacher performance in Aceh Barat Regency, Indonesia. The Merdeka Curriculum, a recent educational reform emphasizing flexibility and student-centered learning, aims to enhance teaching quality and student engagement. Using a quantitative approach, data were collected from 74 high school teachers through structured questionnaires. Statistical analyses, including t-tests and regression, were conducted to assess the impact of curriculum implementation and motivation on teacher performance. Findings reveal that the Merdeka Curriculum significantly improves teacher performance by promoting adaptive teaching practices. Teacher motivation, encompassing intrinsic and extrinsic factors, also positively influences performance, with high motivation levels associated with more extraordinary dedication and effectiveness. The combined analysis indicates that 80.2% of the variation in teacher performance is explained by these factors, suggesting that both curriculum flexibility and motivational support are essential in enhancing educational outcomes. These results offer practical insights for policymakers and educational stakeholders aiming to support teacher engagement and curriculum adaptability.